Meta-Analysis Study: Gender Stereotypes and Bias in School Education Textbooks - Nandi, Ankur; Tarini Hader; Tapash Das (Journal of Multidisciplinary Research and Development, 2024)
Textbooks are essential learning resources for students and have a profound impact on their overall development. They act as agents of social change, influencing students' values, beliefs, and cultural understanding from an early age. Through textbooks and classroom interactions, students absorb gender socialization, societal norms, beliefs, gender roles, identities, inequalities, and biases. Therefore, it is vital to create gender-neutral textbooks, which require a comprehensive analysis of existing materials. As a result, numerous studies have been conducted both locally and internationally to investigate gender stereotypes and biases in textbooks. This meta-analysis aims to examine three specific aspects of the selected research. This study utilizes a meta-analysis design, a type of secondary research that identifies, examines, and interprets all pertinent studies within a particular topic area. The study's findings lay the groundwork for policy changes at the state or national level, ensuring the development and implementation of guidelines that foster gender-neutral content in educational materials. These results are also valuable for textbook development agencies, authors, and educators in creating a gender-sensitive curriculum and textbooks. Ultimately, the implications of this research will help future researchers identify areas for further study.